Experimental and numerical investigation on the geometric parameters of an open-to-atmosphere vortex-based solar particle receiver. (1st September 2022) - Tang, Yining; Sun, Zhiwei; Tian, Zhao; Lau, Timothy; Chinnici, Alfonso; Saw, Woei; Nathan, Graham J.
Highlights: Measurement and simulation of particle egress of an open vortex-based solar receiver. The effect of the amount of airflow ingress and egress, swirl intensity, and flow symmetry on particle egress and swirling flow behaviour. To assess such effect, the aperture-to-cavity diameter ratio, the outlet-to-cavity diameter ratio, and the number of outlets are varied. The particle egress is further reduced due to the swirling flow features. Abstract: We report the influence of the amount of airflow that enters and exits the receiver through the aperture, the swirl intensity, quantified with the use of the Swirl number, and flow symmetry on the measured normalised particle egress and simulated two-phase flow behaviour of an open-to-atmosphere vortex-based solar particle receiver under isothermal conditions. Here, particle egress is defined as the particle loss from the SEVR cavity to the ambient environment through the open aperture. To assess their effect, the geometric parameters of the receiver, including the aperture-to-cavity diameter ratio, the outlet-to-cavity diameter ratio, and the number of outlets, are varied. The laser Mie-scattering method was utilised to measure particle egress through the aperture, and a computational fluid dynamics model was employed and validated to understand the gas-phase flow features within the receiver. The reduction in flow ingress and egress is found to have a dominant effect on mitigating particle egress over that of the Froude number, flow symmetry and swirl intensity. More symmetric flow patterns and weaker swirl intensity are found for multiple-outlet configurations, which results in the reduction of particle egress. All these represent an important advancement toward the optimisation of the geometry of an open-to-atmosphere vortex-based solar particle receiver.